ECRANISATION STUDY OF SOCIAL SETTING OF ME, AND EARL, AND THE DYING GIRL - Regina Ayu Harna Shindy; Romel Noverino (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2021)
Ecranisation is transformation of written text in a novel into motion pictures in film. In so doing, the transformation undergoes three kinds of characteristics which become the main analysis in ecranization study, namely reduction, addition, and variation of change. This article discusses the results of a study on how the three processes in terms of social setting have contributed to the alteration of storyline. Objective data were collected through purposive sampling in this qualitative study from the novel and its film of Me and Earl and the Dying Girl. The results show that the storyline in the film is socially constructed differently from its origin in the novel. It was found that the social behavior and the characterization in the film are not depicted in the same way as in the novel. As the novel is the benchmark for identifying any changes of social setting in the film, it is implied that the transformation has failed in taking into various social aspects as inherent element of storyline in the novel.